A variable nanotrench structure for electric field modulation in AlGaN/GaN devices. (18th February 2019) - Zhang, Anbang; Zhou, Qi; Yang, Chao; Shi, Yuanyuan; Chen, Wanjun; Li, Zhaoji; Zhang, Bo
Abstract: The surface electric field ( E -field) optimization of AlGaN/GaN devices is very important because the two-dimensional electron gas channel is extremely close to the surface. In this work, a novel variable nanotrench (VNT) structure for E -field modulation in AlGaN/GaN devices is proposed and demonstrated. The effectiveness of the VNT-structure in optimizing the surface E -field is investigated by the technology computer aided design simulation. Single step dry etching is developed to fabricate the VNT-structure. Benefitting from the VNT-anode, the fabricated lateral AlGaN/GaN Schottky barrier diode exhibits improved performance including reduced leakage current, increased breakdown voltage, and suppressed electron trapping under reverse bias.